Analisis Kepastian Hukum Pelaksanaan Pendidikan Pancasila Melalui Peraturan Pemerintah Nomor 57 Tahun 2021 tentang Standar Nasional Pendidikan - Subagio, Hani; Hastangka, Hastangka (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to analyze the existence of Pancasila Education before the issuance of Government Regulation Number 57 of 2021 concerning National Education Standards and analysis of legal certainty for the implementation of Pancasila Education through Government Regulation Number 57 of 2021. This study used a qualitative approach, with normative and empirical legal research types. Sources of data obtained from secondary data and primary data. The study results showed that the existence of Pancasila Education experienced various dynamics before the issuance of Government Regulation Number 57 of 2021. Pancasila began to lose its role after issuing Law Number 20 of 2003 concerning the National Education System by eliminating Pancasila Education from primary education to higher education. The main issue of Government Regulation Number 57 of 2021 was based on the findings of inconsistent legal drafting with one another. The issuance of Government Regulation Number 57 of 2021, which did not include the contents of the Pancasila Education material, created legal uncertainty, which had implications for contradicting the laws and regulations on it.